Tindak Tutur dalam Interaksi Penjaja dan Pelanggan: Studi Kasus Pasar Kampung Lalang (Jurnal Simki Pedagogia, 2024)
The speech acts uttered by the speaker often do not match what is received by the recipient of the language (buyer). This problem of meaning is also an obstacle in speech that is not paid enough attention by speakers, both speakers (sellers) and buyers. Language is used as a forum for dialogue between speakers and speakers in buying and selling transactions. The aim of this research is to describe speech acts in the interaction between vendors and customers at Kampung Lalang Market. The method used is a qualitative descriptive method that focuses on reality as the actual situation in the Kampung Lalang market area. The data collection technique is carried out using recording techniques, namely recording speech and speech activities by speakers in the context of buying and selling, recorded with a device or similar. This process is carried out for use by sellers and customers and can be played or listened to many times, thereby facilitating researchers in examining speech acts. The second technique is the observation technique, namely observing something directly, the interaction between sellers and buyers at Kampung Lalang Market. The speech results found in the interaction between the seller and the customer are locutionary acts with the types of statements, questions and commands. Illocutionary speech acts include directive, commissive, declarative and expressive types, as well as perlocutionary speech acts. In this speech the seller and customer use Karo language.